2020
DOI: 10.3390/su12156127
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Use Accounting Platforms in Romania: A Quantitative Study on Sustainability and Social Influence

Abstract: Technological innovation evolves through the use of information systems and this study highlights the intentions of using accounting platforms by conducting a quantitative study on sustainability and its social influence. The purpose of this study is to investigate the factors that influence the acceptance and use by company managers of accounting platforms available online by developing the unified theory of acceptance and use of technology (UTAUT) construct model. The research method used in the quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 52 publications
(86 reference statements)
2
7
0
Order By: Relevance
“…The second and the third influencing factors were social influence and performance expectancy, respectively. The similar results were also found in the study of Cokins et al (2020).…”
Section: Research Framework and Hypotheses Developmentsupporting
confidence: 90%
See 1 more Smart Citation
“…The second and the third influencing factors were social influence and performance expectancy, respectively. The similar results were also found in the study of Cokins et al (2020).…”
Section: Research Framework and Hypotheses Developmentsupporting
confidence: 90%
“…The second and the third influencing factors were social influence and performance expectancy, respectively. The similar results were also found in the study of Cokins et al (2020). Ferri et al (2020) explored the intention to use blockchain from the perspective of auditors in accounting firms in Italy.…”
Section: Research Framework and Hypotheses Developmentsupporting
confidence: 78%
“…This acceleration could lead to a percentage point in annual GDP growth. If this progress were not made, Romania could still reach 12% of GDP with the digital economy, but in this case, the country would be far from what the digital borders of northern Europe mean [52,53]. The advancement of digitalization towards a technology-oriented economy has a role in fueling the necessary growth engine.…”
Section: Iot Technologies In the Sales Process In Europementioning
confidence: 99%
“…The effect of social influence on the behavioral intention to use a new or adapted technology is well known. For example, previous studies have already shown that social influence has an impact on the behavioral intention to use mobile-based assessments [ 37 ], Instagram messaging [ 38 ], web-based banking [ 39 ], eHealth services [ 40 ], social media [ 41 ], e-government [ 42 ], e-learning [ 43 ], and accounting platforms [ 44 ]. Although this review is not exhaustive and includes only a fraction of the studies that have investigated the relationship between social influence and the behavioral use intention, to the best of our knowledge, the relationship between social influence and behavioral intention to use PRWs has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%